PENGARUH PERAN KADER POSYANDU TERHADAP PEMANFAATAN PELAYANAN POSYANDU DALAM PENIMBANGAN BALITA DI KOTA PADANGSIDIMPUAN TAHUN 2015 - Devi Sagita Saragi (Jurnal Gentle Birth, 2020)
ABSTRACTNationally nutritional status of children in some regions in Indonesia is still a problem. There is or no child’s nutrition problem in an area is not far from the Posyandu cadre role. The cadre rolein Posyandu organization is very large not only as health information givers to the society to come toPosyandu. The purpose of this reseachis to know the influence of the Posyandu cadre role to the utilization of Posyandu service in  weighing of toddler in Padangsidimpuan City in 2015. This reseach  is a survey with using explanatory reseach approach that aims to explain the influence of the Posyandu cadre role to the utilization in weighing of toddler in Padangsidimpuan City in 2015. The population of this reseach is all the Posyandu in Padangsidimpuan City as many as 76 Posyandu. In Collecting this data, it is used questionnares. The data is analized by using logistic regression test.The results of the reseach showsthat the utilization of Posyandu service in weighing of toddler still low at 35.5% of the total 76 Posyandu, and statistically the most dominant influencing variable is the keepingrole of mother’s activity with regression coefficient 27,722.The cadre has a very important role on the utilization of Posyandu service in weighingof toddler. It is suggested the cadre should more active ininviting mothers to come to the Posyandu and increasing mother’s knowledge so that they bring their children to the Posyandus. Keywords: Role, Posyandu’s cadre, Posyandu’s services, weighing of toddler